여성 환자에서 고전적 갑상선 절제술과 로봇-내시경적 갑상선 절제술 후 오심 구토 발생 빈도 비교 - Lee, A Ram (The Graduate School, Ajou University, 2013)
-ABSTRACT- Comparison of the incidence of postoperative nausea and vomiting Between women undergoing open or robot-assisted thyroidectomy Background Open thyroidectomy is associated with a high incidence of postoperative nausea and vomiting (PONV) of up to 70 %. Use of the recently introduced robot-assisted endoscopic thyroidectomy using a gasless transaxillary approach has been increasing because of its several advantages over open thyroidectomy. This study compared the incidence of PONV in the womenwho underwent open or robot-assisted thyroidectomy. Materials and methods This prospective, double-blinded study enrolled 170 women 20-60 years of age who were scheduled for conventional open thyroidectomy (Group O) or robot-assisted thyroidectomy (Group R). A standard anesthetic technique, including sevoflurane and air in oxygen, was used. During 0-24 postoperative periods, the presence and severity of PONV (nausea, retching/vomiting), severity of pain, need for rescue antiemetics and the incidence ‘satisfied’ patient were evaluated. Results During 0-6 hpostoperative periods, the incidence of PONV and mean pain score (40.0% vs. 51.8% and 4.2 vs. 4.8 in Group R and O, respectively) were not significantly different between groups. During 6-24 hpostoperative periods, the incidence of PONV (18.8% vs. 44.7%), severe emesis (11.8% vs. 29.4%) and mean pain score (2.8 vs. 3.8) were significantly lower in Group R compared to Group O, respectively. Overall, the incidence of PONV (42.4% vs. 63.5%) and severe emesis (20.0% vs. 43.5%) were significantly lower in Group R compared to Group O. The incidence of ‘satisfied’ patient during 0-6 h and 6-24 postoperative periods (55.3% vs. 28.2% and 82.4% vs. 58.8%) were significantly higher in Group R compared to Group O. Conclusion Robotic thyroidectomy reduced the incidence and severity of PONV compared to open thyroidectomy during 0-24 postopertive periods. ________________________________________ KeyWords Robotic•Openthyroidectomy, Postoperative nausea and vomiting
학위논문(석사)----아주대학교 일반대학원 :의학과,2013. 8
Keywords: Robotic Openthyroidectomy; Postoperative nausea and vomiting